Geomorphological Processes Associated with an Ice-Marginal Lake at Bridge Glacier, British Colombia - Ryder, June (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTFour well-defined strandlines mark the former extent and drawdown phases of an ice-marginal lake that was impounded by Bridge Glacier during the Little Ice Age. 14C dates, tree-ring counts and historic air photographs indicate that the lake stood at the highest strandline (L1) for about 550 years, and at the lower strandlines for only a few decades in total. Estimates of rates for geomorphic processes are based on absolute chronology, ground measurements and photogrammetry: benches along L1 may have been cut into bedrock and till at rates of about 3.6 and 7.3 cm yr~1 respectively; a spillway channel was incised into a lateral moraine at 2.2 m yr\ and mean bedload transport to a delta from a 6.25 km2 ice-covered sub-basin was about 945 m3 yr '. Major floods from the stable, rock-cut spillway of the highest lake, that may have been caused by temporary damming of the lake outlet by snowbanks or lake ice, constructed a large fan on the main Bridge Glacier outwash apron. The lower lakes probably drained catastrophically due to failure of moraine and ice dams, but the resulting floods were rapidly attenuated downstream.